Factors associated with inaccurate size estimation of colorectal polyps: A multicenter cross‐sectional study. Issue 8 (25th February 2021) - Utsumi, Takahiro; Horimatsu, Takahiro; Nishikawa, Yoshitaka; Teramoto, Akira; Hirata, Daizen; Iwatate, Mineo; Tanaka, Shinwa; Ikezawa, Nobuaki; Esaki, Masaya; Osera, Shozo; Ebisutani, Chikara; Agatsuma, Nobukazu; et al.
Abstract: Background and Aim: Accurate polyp size estimation is essential in deciding the therapeutic strategy of colorectal polyps and endoscopic surveillance intervals. However, many endoscopists frequently make incorrect size estimations without being aware of their errors. This cross‐sectional study aimed to clarify the characteristics of endoscopists associated with inaccurate estimation. Methods: We previously conducted a web trial involving 261 endoscopists in 51 institutions in Japan to assess their ability to estimate polyp size. Participants answered questions about polyp size using visual estimates in a test involving images of 30 polyps. Here, we investigated the relationships between inaccurate size estimation and the backgrounds of participants. The rates of overestimation and underestimation of polyp size were also compared to clarify any trends in the answers of participants with low accuracy (< 50%). Results: Multivariable logistic regression analysis revealed that the number of colonoscopic procedures in the past year was the only factor associated with a low accuracy of polyp size estimation (odds ratio 0.750, 95% confidence interval 0.609–0.925; P  = 0.007). Endoscopists with low accuracy had a greater tendency to overestimate polyp size (42.3% overestimation and 21.2% underestimation, P  < 0.001) compared with other endoscopists (16.6% overestimation and 17.9% underestimation, P  = 0.951). Conclusions: Endoscopists with limited experience of colonoscopy in the past year were more likely to make frequent errors in size estimation. Furthermore, endoscopists making inaccurate size estimations had a propensity to overestimate polyp size.